If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -28 = 24 Reorder the terms: -28 + 6x = 24 Solving -28 + 6x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + 6x = 24 + 28 Combine like terms: -28 + 28 = 0 0 + 6x = 24 + 28 6x = 24 + 28 Combine like terms: 24 + 28 = 52 6x = 52 Divide each side by '6'. x = 8.666666667 Simplifying x = 8.666666667
| (4x+3)(2x+7)= | | log(logx-1)=0 | | 5x-(2x+x)=x+(3x-5) | | 4+P*0.0381/12 | | 61y=10 | | -7f=2*-7+8 | | 7(6x-5)+15x= | | 2l+2(70)=800 | | -9/7=-2x-x | | x-6=x-9 | | (w-5)(w+5)= | | 8=-5t-2 | | 4=3x/4-2 | | -2/x | | -125/x=-21 | | 6(2x+3)=24 | | -6u-30=0 | | 3z^2-10z+3=0 | | 4t+12=0 | | -0.75x-47.77=-27.27-4.85x | | 1-1/4 | | 4z^2-4z-48=0 | | -2-(-3)-3= | | 1/2-2/1+3/4 | | 8+x-8+2+6+x-4= | | 2n-4(n-6)=1/2(-4n-5) | | 6t-20=-8 | | n^3-20n^2-5=0 | | 5(3b-3)-3(3b-7)=12 | | 6x^2+-7x^2= | | -14=-8u+15 | | -0.5t-3.7=-0.7 |